2022
DOI: 10.3390/molecules27207134
|View full text |Cite
|
Sign up to set email alerts
|

Euodia daniellii Hemsl. Extract and Its Active Component Hesperidin Accelerate Cutaneous Wound Healing via Activation of Wnt/β-Catenin Signaling Pathway

Abstract: The activation of the Wnt/β-catenin signaling pathway plays a key role in the wound-healing process through tissue regeneration. The extract of Euodia daniellii Hemsl. (E. daniellii), a member of the Rutaceae family, activates the Wnt/β-catenin signaling pathway. However, the function of E. daniellii in wound healing has not yet been elucidated. We performed a migration assay to determine the wound-healing effect of E. daniellii extract in vitro using human keratinocytes and dermal fibroblast. In addition, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In vitro anti-inflammatory studies showed that PVA/AH hydrogel inhibited heat-induced HRBC hemolysis, hypotonicityinduced hemolysis, and egg albumin denaturation better than PVA/ A. The results indicate that H may play a significant antiinflammatory role (51,52) in membrane stabilization of HRBC.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In vitro anti-inflammatory studies showed that PVA/AH hydrogel inhibited heat-induced HRBC hemolysis, hypotonicityinduced hemolysis, and egg albumin denaturation better than PVA/ A. The results indicate that H may play a significant antiinflammatory role (51,52) in membrane stabilization of HRBC.…”
Section: Discussionmentioning
confidence: 88%
“…In vitro anti-inflammatory studies showed that PVA/AH hydrogel inhibited heat-induced HRBC hemolysis, hypotonicity-induced hemolysis, and egg albumin denaturation better than PVA/A. The results indicate that H may play a significant anti-inflammatory role ( 51 , 52 ) in membrane stabilization of HRBC. In addition, since lysosomal membrane and HRBC membrane have the same components, thus H may have a significant role in the integrity of cell membrane damage ( 53 , 54 ), and inhibit lysosomal lysis during inflammation and the release of enzymes ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 90%
“…The Wnt/β-catenin signaling pathway plays an important role in HF regeneration and wound healing [46][47][48]. Accumulating evidence has demonstrated that activation of the Wnt/β-catenin signaling pathway could promote wound healing [49,50]. During HF morphogenesis, the dermis provides the ' rst dermal signal' that initiates the formation of epidermal placodes, and sustained β-catenin activity in the dermis leads to larger HF placodes and accelerates differentiation of HFs [49,51].…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt/β-catenin pathway is a well-known key player for enhancement of the overall healing process involving tissue regeneration via crosstalk with other signaling pathways [97]. The activation of the Wnt/β-catenin pathway elicits a range of healing responses, including the promotion of angiogenesis [98,99], enhancement of fibroblast migration, proliferation, and differentiation [1,97], stimulation of keratinocyte proliferation and differentiation [100,101], facilitation of re-epithelialization [102,103], and the induction of wound-induced hair folliculogenesis [104,105]. A cell tracing study reported that constitutive activation of β-catenin in DS not only generated ectopic hair follicle outgrowth, endowing DSCs with hair-inducing ability, but also induced cell-autonomous progressive skin fibrosis in the dermis, where the excessive fibroblasts largely originated from the DS [8].…”
Section: Potential Role Of Dermal Sheath Cells In Fibrosismentioning
confidence: 99%